Women's Barracks: The original 1950 tale of life and love in the free french army - Torres, Tereska; Mayne, Judith (The Feminist Press at CUNY, 2012)
This novel—based on the author's real-life experiences—is credited as the first candidly lesbian novel, originally published in 1950, that “scandalized mid-century America” (The New York Times).As the Blitz rains down over London, taboos are broken, affairs start and stop, and hearts are won and lost. This account of life among female Free French soldiers in a London barracks during World War II sold four million copies in the United States alone and many more worldwide. Women’s Barracks was banned for obscenity in several states and denounced by the House Select Committee on Current Pornographic Materials in 1952 as an example of how the paperback industry was “promoting moral degeneracy.” In spite of such efforts—or perhaps, in part, because of them—the novel became a record-breaking bestseller and inspired a whole new genre: lesbian pulp.Femmes Fatales restores to print the best of women’s writing in the classic pulp genres of the mid-20th century. From mystery to hard-boiled noir to taboo lesbian romance, these rediscovered queens of pulp offer subversive perspectives on a turbulent era.
Keywords: 1900-1999; 1940-1949; amour interdit; approches et analyses; europe; hétérosexisme; identités LGBTQIA2+; littérature; patriarcat; personnes lesbiennes; pulp lesbien; périodes historiques; royaume-uni; régions géographiques; sexualité; systèmes d'oppressions; thématiques

Make Room for Daddy: Anxious Masculinity and Emergent Homophobias in Neopatriarchal Politics - Stein, Arlene (Gender and Society, 2005)
What are the sources of continuing antipathy toward homosexuality, and what might they tell us about changing forms of American masculinity? This article documents some emergent homophobias circulating among conservative activists in relation to campaigns against gay rights in the early 1990s and against gay marriage in 2004. As feminist critiques of traditional masculinity make their way into conservative rhetoric and as men struggle to define a role that maintains male authority without sounding overly authoritarian, new forms of homophobia have emerged that are compatible with conservatives' quest to be seen as compassionate protectors of the family.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; anthropologie; approches et analyses; cours; discipline; homophobie; hétérosexisme; masculinité; militance; patriarcat; premier cycle; périodes; périodes historiques; régions géographiques; sciences humaines; soc2014; systèmes d'oppressions; thématiques; violences; états-unis

The Quest for Modern Manhood: Masculine Stereotypes, Peer Culture and the Social Significance of Homophobia - Plummer, David C. (Journal of Adolescence, 2001)
This paper explores the use of homophobic terms by boys and young men and the meanings they invoke when using them. Highly detailed interviews were conducted with young men from diverse backgrounds about their own experiences while growing up and their observations of schools, teachers, family and peers. Homophobia was found to be more than a simple prejudice against homosexuals. Homophobic terms like “poofter” and “faggot” have a rich developmental history and play a central role in adolescent male peer-group dynamics. Homophobic terms come into currency in primary school. When this happens, words like poofter and faggot rarely have sexual connotations. Nevertheless, far from being indiscriminate terms of abuse, these terms tap a complex array of meanings that are precisely mapped in peer cultures, and boys quickly learn to avoid homophobia and to use it decisively and with great impact against others. Significantly, this early, very powerful use of homophobic terms occurs prior to puberty, prior to adult sexual identity and prior to knowing much, if anything, about homosexuality. An effect of this sequence is that early homophobic experiences may well provide a key reference point for comprehending forthcoming adult sexual identity formation (gay or not) because powerful homophobic codes are learned first.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; approches et analyses; australie; cours; discipline; homophobie; hétérosexisme; masculinité; nouvelle-zélande; océanie; patriarcat; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; soc2014; sociologie; systèmes d'oppressions; thématiques; violences

L'homosexualité masculine et les discours sur le sexe en contexte montréalais de la fin du XIXe siècle à la Révolution tranquille - Hurteau, Pierre (Histoire sociale / Social History, 1993)
La croyance populaire ainsi qu'une certaine théologie accordent souvent au discours religieux sur l'homosexualité une permanence doctrinale qu'il n'a pas. Les mythes populaires ont longtemps attribué la stigmatisation sociale de l'homosexualité au récit de Sodome. La critique historique du rapport entre religion et homosexualité permet cependant de mettre en évidence le caractère construit de ce discours et ses rapports avec le juridique et le médical. Le présent article veut établir de quelle manière ces discours ont pu s'élaborer au Québec, et particulièrement dans la région montréalaise, entre la fin du XIXe siècle et la Révolution tranquille. L'approche historique suggère une nouvelle herméneutique qui met en lumière les véritables impulsions qui sous-tendent le discours religieux sur l'homosexualité. Popular belief and certain types of theology often ascribe a continuity of doctrine to the religious discourse on homosexuality which, in fact, this discourse does not have. Popular myths have long attributed the social stigma of homosexuality to the story of Sodom. Historical criticism of the relationship between religion and homosexuality will bring to the fore the social construction of the religious discourse and its historical connections with the secular discourses of law and medicine. The following article will try to demonstrate how these discourses developed in Quebec, and particularly in the Montreal region, from the end of the nineteenth century to the Quiet Revolution. The historical approach taken here puts forward a new interpretation that brings to the light the real motivations that underlie the religious discourse on homosexuality.
Keywords: 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; 1950-1959; 1960-1969; LGBTQIA2+; Québec (Province); amériques; approches et analyses; canada; cours; discipline; discours dominant; discours religieux; his4860; histoire; histoire et politique; homophobie; homosexualité; hétérosexisme; montréal; patriarcat; premier cycle; périodes historiques; québec; religion; régions géographiques; révolution tranquille; sciences humaines; sexualité; soc2014; sofia; systèmes d'oppressions; thématiques

Microcosm - Duffy, Maureen (Virago, 1989)
À la House of Shades, Matt, un philosophe de bar, tente de donner un sens aux vies disparates qui se croisent ici : de Judy qui réserve elle-même et ses plus beaux atouts pour un amant du samedi soir, de Steve le professeur de gym qui redoute une chance. rencontre avec une élève dans cet environnement crépusculaire, et avec Matt elle-même, qui a besoin de ces échanges indirects malgré la sécurité de sa relation avec Rae et son sentiment que ce sanctuaire lesbien est aussi une prison, renforçant la culpabilité et l'éloignement des rues de la ville au-delà. Ailleurs, il y a des femmes comme Marie, prisonnière d'un mariage non désiré et incapable d'admettre sa sexualité, et Cathy, pour qui découvrir qu'elle n'est pas « la seule au monde » est une affirmation de son existence. Avec sa structure et son style innovants, reflétant parfaitement les voix et les expériences des femmes contraintes par la société à vivre en marge, The Microcosm reste aussi puissant aujourd'hui que lors de sa première publication en 1966.
Première édition: 1966
Keywords: 1900-1999; 1960-1969; approches et analyses; hétérosexisme; identités LGBTQIA2+; patriarcat; personnes lesbiennes; périodes historiques; roman; sexualité; systèmes d'oppressions; thématiques; travail; violences

Les lesbiennes et le féminisme - Roy, Carolle (Éditions Saint-Martin, 1985)
Section: 142 pages ; 23 cm
Keywords: 1900-1999; 1970-1979; 1980-1989; LGBTQIA2+; approches et analyses; cours; discipline; europe; france; hétérosexisme; identités LGBTQIA2+; lesbianisme; patriarcat; premiers peuples; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques